2011
DOI: 10.12968/bjon.2011.20.9.555
|View full text |Cite
|
Sign up to set email alerts
|

Childhood sexual abuse: help make it ‘Safe to Say’

Abstract: Childhood sexual abuse remains a taboo subject and requires sensitive handling by committed and caring services (Scottish Executive, 2004). By introducing a training programme, Safe to Say, the Scottish Association of Mental Health aims to improve the confidence and competence of healthcare workers when faced with the sensitive disclosure of childhood abuse. This article aims to explore the effects of childhood sexual abuse and the attitudes of health professionals when faced with adult survivors disclosing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Walsh and Major (2011) have questioned the preparation of students to work with service users who have experienced childhood sexual abuse. Amongst qualified staff, reluctance to ask about sexual abuse and lack of training to work with this issue has been identified (Hepworth and McGowan, 2013;Tong and Gillespie, 2011). Several authors have identified problems surrounding nurse attitudes to service users with a diagnosis of personality disorder as well as a lack of training and supervision to work therapeutically with this group (Weight and Kendal, 2013;O'Connell and Dowling, 2013;Westwood and Baker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Walsh and Major (2011) have questioned the preparation of students to work with service users who have experienced childhood sexual abuse. Amongst qualified staff, reluctance to ask about sexual abuse and lack of training to work with this issue has been identified (Hepworth and McGowan, 2013;Tong and Gillespie, 2011). Several authors have identified problems surrounding nurse attitudes to service users with a diagnosis of personality disorder as well as a lack of training and supervision to work therapeutically with this group (Weight and Kendal, 2013;O'Connell and Dowling, 2013;Westwood and Baker, 2010).…”
Section: Introductionmentioning
confidence: 99%